Chikungunya virus-associated death in Malaysia - Sam, I.C.; Kamarulzaman, Adeeba; Ong, G.S.Y.; Veriah, R.S.; Ponnampalavanar, S.; Chan, Y.F.; AbuBakar, Sazaly (2007)
Chikungunya virus (CHIKV) is a mosquito-borne alphavirus which causes fever, rash, and arthralgia. In the past, life-threatening complications were very rarely reported. However, during the recent worldwide outbreaks, there have been several reports of unusually severe complications and deaths. Malaysia is experiencing a nationwide outbreak of CHIKV, with over 10 000 patients affected since April 2008. We report the first case of culture-confirmed CHIKV-associated death in Malaysia, in a patient with fever, rash, acute exacerbation of pre-existing heart failure, rhabdomyolysis, and multiple organ failure. CHIKV infections may cause atypical, severe or fatal presentations.